Wonderlands of the avant-garde : technology and the arts in Russia of the 1920s - Vaingurt, Julia (Studies in Russian literature and theory., 2013)
In postrevolutionary Russia, as the Soviet government was initiating a program of rapid industrialization, avant-garde artists declared their intent to serve the nascent state and to transform life in accordance with their aesthetic designs. In spite of their professed utilitarianism, however, most avant-gardists created works that can hardly be regarded as practical instruments of societal transformation. Exploring this paradox, this book claims that the artists' investment of technology with aesthetics prevented their creations from being fully conscripted into the arsenal of political hegemony. The purposes of avant-garde technologies, the author contends, are contemplative rather than constructive. Looking at Meyerhold's theater, Tatlin's and Khlebnikov's architectural designs, Mayakovsky's writings, and other works from the period, the author offers a reading of an exceptionally complex moment in the formation of Soviet culture. --